LANDASAN FILOSOFIS MAZHAB HUKUM PROGRESIF: TINJAUAN FILSAFAT ILMU - Rizal Mustansyir (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2008)
AbstractThe discourse on the progressive law blows up recently. Theassumption which declared that “law is for human” strengthened the progressive law position. This progressive law condition contradicts to the positive law which pretend to be formalistic. The law environment in Indonesia which is coloured with crisis of distrust makes the idea of progressive law accepted enthusiasticly. While the view that “law as a process, law in the making” takes the idea of progressive law as an actual thing. The problem is that the progressive law has not been established a theory yet. It still need to be explored intensively. This passage examines the progressive law in the perspective of philosophy of science, because whatever theory or sosial movement must have had a philosophical ground.Keywords: The progressive law, Perspective of philosophy ofscience